Teologi Surat al-Maun dan Praksis Sosial Dalam Kehidupan Warga Muhammadiyah - Andri Gunawan (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2018)
Abstract:One of the basic foundations of the Muhammadiyah movement is the theological power of Surat al-Ma'un taught by Kyai Ahmad Dahlan, Founder of Muhammadiyah. Ahmad Dahlan interpreted Al-Ma'un into three main activities, namely: education, health and the sponsorship of the poor also transformed religious understanding from mere sacred doctrines and